Uses Flashcards to Increase the Vocabulary of Elementary School Students - Sumbertada, Ketut (Jurnal Penelitian Mahasiswa Indonesia, 2024)
The current post-pandemic Covid-19 situation has a very significant impact on people around the world. Education in this situation is required to change mindsets and learning systems that prioritize the use of technology that is currently developing in the digital 5.0 era. This study aims to determine the benefits of using Flashcards in the learning process for 4thgrade elementary school students at SDN 3 Alasangker. This research is also intended to find out the problems faced by teachers and students, as well as the benefits of applying Flashcards in the learning process. In collecting data, the researcher applied several data collection instruments consisting of interviews, observations, document analysis, and giving questionnaires. The subjects of this study were grade 4 elementary school students. The results of this study indicate that most students find it easier to remember and memorize vocabulary by using flashcards than being explained directly.